2022
DOI: 10.3390/ijms23126775
|View full text |Cite
|
Sign up to set email alerts
|

Does the Freeze–Thaw Technique Affect the Properties of the Alginate/Chitosan Glutamate Gels with Posaconazole as a Model Antifungal Drug?

Abstract: Hydrogels are semi-solid systems with high flexibility, which, due to holding large amounts of water, are similar to natural tissues and are very useful in the field of biomedical applications. Despite the wide range of polymers available to form hydrogels, novel techniques utilized to obtain hydrogels with adequate properties are still being developed. The aim of this study was to evaluate the impact of the freeze–thaw technique on the properties of cryogels based on sodium alginate and chitosan glutamate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The number of crosslinked molecules forming an insoluble gel fraction is reflected by the gel content of a hydrogel, while the non-crosslinked portion of the hydrogel dissolves upon immersion in a solvent, leading to a reduction in the sample weight [ 116 ]. In addition to PVA crosslinking, freeze–thaw cycles have been demonstrated to promote the formation of intermolecular bonds in Alg [ 84 , 117 , 118 ], collagen [ 101 , 119 ] and hyaluronic acid [ 100 , 120 ]. The biohybrid hydrogel membranes were found to exhibit lower values for the gel fraction when compared to the corresponding hybrid hydrogel membranes, as expected from previous assays.…”
Section: Resultsmentioning
confidence: 99%
“…The number of crosslinked molecules forming an insoluble gel fraction is reflected by the gel content of a hydrogel, while the non-crosslinked portion of the hydrogel dissolves upon immersion in a solvent, leading to a reduction in the sample weight [ 116 ]. In addition to PVA crosslinking, freeze–thaw cycles have been demonstrated to promote the formation of intermolecular bonds in Alg [ 84 , 117 , 118 ], collagen [ 101 , 119 ] and hyaluronic acid [ 100 , 120 ]. The biohybrid hydrogel membranes were found to exhibit lower values for the gel fraction when compared to the corresponding hybrid hydrogel membranes, as expected from previous assays.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that all the prepared formulations had a similarity factor f2 < 50 and a difference factor f1 > 15, indicating that the F-T technique significantly affected the POS release profile. In addition, alginate/chitosan glutamate Drug delivery [149] -The internal morphology observed using SEM did show some phase separation between the liquid and solid phases in the hydrogel composite. -The degree of swelling of the composite hydrogel showed an average value above 200%, which indicated a good ability to absorb wound exudate.…”
Section: Wound Dressing [79]mentioning
confidence: 99%
“…Typical examples include the frozen Tofu (protein), gelatin, PVA, and alginate. [ 90‐91 ] The dynamic covalent hydrogel networks can also be relaxed by stimulation during freezing, and obtain the macroporous hydrogels. The corresponding mechanism will be further discussed in the following sections.…”
Section: Macroporous Hydrogels Prepared By Ice Templatingmentioning
confidence: 99%